Some cyano-substituted spiro-linked pyrazolines and pyrrolidines with antimicrobial activity - Meshcheryakova, Anna A.; Borisova, Svetlana Vasilievna; Konstantinova, Ekaterina A.; Vidlatskaya, Daria V.; Burygin, Gennady L.; Sorokin, Vitaly Viktorovich (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология)
This work summarizes one-pot synthetic approaches to spiro-fused (di)azoles, which are promising in terms of studying biological activity. Proposed approaches involve condensation reactions of (hetero)cyclic ketones, methylene active moieties, and N-nucleophiles, occurring under mild conditions by both stepwise and concerted mechanisms. The antimicrobial activity of signals from the proposed approaches of cyanosubstituted spiro-membered pyrazolines and pyrrolidines against gram-negative (P. aeruginosa, E. coli) and gram-positive (S. aureus) losses has been studied (EC50 determination (μg/ml)).The well-known component of broad-spectrum antimicrobial drugs, ciprofl oxacin, has been used as a control. It has been found that 3-amino-2-(4-nitrophenyl)-1,2-diazaspiro[4.5]dec-3-ene-4-carbonitrile exhibits the greatest inhibitory eff ect against selected gram-negative bacteria. In this case, the phenyl substituent at the second nitrogen atom of the pyrazoline ring plays an important role, since its replacement with an aroyl fragment reduces the studied eff ect by several tens of times, regardless of the type of the second ring. Substituted spiroindolinopyrrolizidinedicarbonitriles, containing cyano groups at the 2nd carbon atom of the pyrrolizidine ring and a phenyl substituent at the fi rst, also exhibit a moderate and high inhibitory eff ect. For pairs with the same type of substituent position, compounds containing a 3,4 Cl2 substituent in the phenyl fragment have the greatest antimicrobial activity.